1980
DOI: 10.3168/jds.s0022-0302(80)82881-5
|View full text |Cite
|
Sign up to set email alerts
|

Fat in Lactation Rations : Review

Abstract: Recent research has demonstrated the effectiveness of added fat in diets to maintain milk production and fat percent. Much of the earlier work which indicated that fat affects digestion negatively may not be applicable because of great differences in the nature of diets and fats fed and especially in total feed intake. Nevertheless, much remains to be learned about interactions of fat, fiber, calcium, and rumen microorganisms if feeding of fat is to be maximized. The uniquely high acidity in the duodenum combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
397
7
58

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 802 publications
(494 citation statements)
references
References 108 publications
32
397
7
58
Order By: Relevance
“…No entanto, dependendo do teor ou fonte de gordura utilizados, o desempenho do animal pode ser comprometido, pois ácidos graxos polinsaturados de cadeia longa livres são potencialmente tóxicos aos microrganismos ruminais, particularmente aos protozoários e bactérias celulolíticas (Palmquist & Jenkins, 1980), contribuindo para a redução na atividade microbiana e subseqüente digestão (Gibb et al, 2005). Não houve diferença entre os tratamentos para RCQ, RCF e QR, cujas médias observadas foram de 48,9, 47,7 e 2,4%, respectivamente (Tabela 3).…”
Section: Resultsunclassified
“…No entanto, dependendo do teor ou fonte de gordura utilizados, o desempenho do animal pode ser comprometido, pois ácidos graxos polinsaturados de cadeia longa livres são potencialmente tóxicos aos microrganismos ruminais, particularmente aos protozoários e bactérias celulolíticas (Palmquist & Jenkins, 1980), contribuindo para a redução na atividade microbiana e subseqüente digestão (Gibb et al, 2005). Não houve diferença entre os tratamentos para RCQ, RCF e QR, cujas médias observadas foram de 48,9, 47,7 e 2,4%, respectivamente (Tabela 3).…”
Section: Resultsunclassified
“…In addition, A:P ratio was also highest in OIL and lowest in MEG(P < 0.05). Palmquist and Jenkins(1980) observed that A : P ratio in the rumen was reduced by fat supplementation. Generally, characteristic of ruminal fermentation in cows have not been altered by supplementation of as much as 6% of dietary fat (Schauff and Clark, 1989;Klusmeyer et al, 1991;Drackley and Elliott, 1993).…”
Section: Resultsmentioning
confidence: 74%
“…However, dietary fat supplements are known to cause negative modification to fermentation and nutrient digestion in the rumen. Reductions have been demonstrated in fibre and organic matter digestion, methanogenesis, ammonia concentrations and acetate:propionate value (Devendra and Lewis, 1974;Palmquist and Jenkins, 1980). Therefore, various methods such as formaldehyde-treated emulsions of fat in proteins (Scott et al, 1971), calcium soaps (Jenkins and Palmquist, 1982), heat treatment (Tice et al, 1994), fatty acyl amides (Fotouhi and Jenkins, 1992), the crystalline hydrogenated fat (Elliott et al, 1994) and feeding whole oilseeds (Scollan et al, 2001) for protecting fat sources from rumen metabolism, which offers the possibility that fat sources fed in such a form may interfere less with rumen metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…O consumo de pasto pelas novilhas que recebiam gordura provavelmente visou a saciar a sua demanda energética, pois a ingestão de dietas com gordura pode fazer com que os animais em pastejo tenham essa demanda atendida mesmo ingerindo uma quantidade menor de pasto (GAGLIOSTRO & CHILLIARD, 1992). A quantidade ingerida de gordura, 3% na MS da dieta, foi inferior ao limite de 5 a 6% na MS da dieta (PALMQUIST & JENKIS, 1980). Conforme esses autores, valores maiores de gordura podem afetar a fermentação ruminal, pela formação de uma camada gordurosa em torno das partículas de fibra, dificultando a ação das bactérias celulolíticas no rúmen.…”
Section: Resultsunclassified